2014
DOI: 10.1111/jvim.12494
|View full text |Cite
|
Sign up to set email alerts
|

Functional Phenotype and its Correlation with Therapeutic Response and Inflammatory Type of Bronchoalveolar Lavage Fluid in Feline Lower Airway Disease

Abstract: BackgroundCurrently, functional assessment to monitor therapeutic response in feline lower airway disease (FLAD) has limited application.ObjectivesTo evaluate if expiratory indices derived from pseudo‐tidal breathing flow‐volume loop (pTBFVL) representing lower airway obstruction would decrease after clinical improvement and to investigate the correlation between functional phenotype and inflammatory cell type in bronchoalveolar lavage (BAL) fluid.AnimalsNineteen client‐owned cats with FLAD.MethodsProspective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 39 publications
8
27
0
Order By: Relevance
“…Airway eosinophilia was the most common IAD (47%) in our group of cats, which is similar to recent studies, 8,11,13,15,20 but other, primarily older, publications 1‐3 have reported eosinophilic inflammation in a smaller proportion (24%‐32%) of cats evaluated. This difference might suggest an increasing trend toward eosinophilic disease in cats, which is interesting considering that allergic and asthmatic diseases have been increasing in people 21 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Airway eosinophilia was the most common IAD (47%) in our group of cats, which is similar to recent studies, 8,11,13,15,20 but other, primarily older, publications 1‐3 have reported eosinophilic inflammation in a smaller proportion (24%‐32%) of cats evaluated. This difference might suggest an increasing trend toward eosinophilic disease in cats, which is interesting considering that allergic and asthmatic diseases have been increasing in people 21 .…”
Section: Discussionsupporting
confidence: 91%
“…Neutrophilia predominates in the allergic disease process in horses partially because of IL‐4‐mediated release of neutrophilic chemotactic factors, 31 and the severity of disease correlates to some extent with the severity of airway neutrophilia 32 . The cytokine milieu in the respiratory tract of cats with naturally occurring airway disease has not been evaluated, but 1 study did associate the magnitude of airway inflammation with the clinical and radiographic severity of disease, 3 and airway responsiveness has been correlated with the severity of airway inflammation 8,15 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations